Curriculum Implementation of Sou (School of Universe) in Bogor - Fatmawati Fatmawati (Budapest International Research and Critics University, 2019)
The emergence of natural schools is considered capable of being an alternative in improving the quality of education. This study aims to describe the curriculum used in the Sougogors natural school and examine the structure listed in the natural school. The method used in this study is a qualitative method with a type of descriptive research. Data collection techniques used are observation and interviews. The subjects in this study are supervisors, principals, teachers, school committees and some high-class students. The results showes that the curriculum used in the SoUbogor natural school was called AKAR ALAM. AKAR ALAM have four concepts, namely 1) moral curriculum; 2) leadership curriculum; 3) logic curriculum; 4) business curriculum. Of the four curriculum concepts, AKAR ALAM has similarities with the structure of the National curriculum. Kurikuum natural school is considered able to improve education quality because it is expected that other schools can make the curriculum a reference in learning.